Faktor-Faktor yang Mempengaruhi Hasil Belajar Mata Pelajaran Pendidikan Agama Islam - Muhammad Syahdan Majid; Abdi Azizurahman (UMSU, 2022)
Nowadays, the prevalence of juvenile delinquency such as brawls between students, drugs, and free sex shows a negative impact on the progress of this civilization. This incident certainly shows fewer results than students' Islamic education in schools. It becomes homework for Islamic religious education as a subject that contains religious values, morals, and ethics. This subject is a leading position in the moral development of students. Several internal and external influences that affect learning outcomes include physical, psychological, fatigue, family, school, and community. The most influencing factor in student learning outcomes is the family factor.